Evaluating the Implementation of the Formal Diniyah Education Curriculum at Al-Junaidiyah Biru Modern Islamic Boarding School - kasmahh, kasmah; Sulaeman; Abd. Hafid; A. Sri Mardiyanti Syam (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2025)
This research provides a systematic evaluation of the implementation of the Formal Diniyah Education (PDF) program, utilizing a case study of the Al-Junaidiyah Biru Modern Islamic Boarding School in Bone Regency, South Sulawesi. The PDF Ulya program represents a significant policy innovation within Indonesian Islamic education, designed to integrate the rich scholarly traditions of the pesantren with the standardized frameworks of national formal education. Employing a qualitative methodology structured by the CIPP (Context, Input, Process, Product) evaluation model, this study conducts a comprehensive analysis of the program's components and outcomes. The results reveal that the Al-Junaidiyah Biru Islamic Boarding School has effectively instituted a successful model of the PDF Ulya program. This achievement is attributable to the synergistic alignment of four key components: Context: The institutional environment was highly conducive to innovation, characterized by a modern identity, a robust digital presence, and an embedded culture of high achievement; Input: The curricular input was centered on a sophisticated design that integrates three foundational pillars: the traditional pesantren curriculum based on classic Islamic texts (kitab kuning), the standard curriculum mandated by the Ministry of Religious Affairs, and the national general curriculum; Process: The implementation process incorporated innovative pedagogical methods coupled with a nationally standardized assessment mechanism, the Imtihan Wathani; Product: The resulting product—the program’s graduates—demonstrates exceptional outcomes, evidenced by numerous national and international accolades, most notably the successful admission of alumni into Al-Azhar University in Cairo. In conclusion, the PDF Ulya program at Al-Junaidiyah Biru exemplifies a successful paradigm for modernizing pesantren education, adeptly balancing contemporary standards with the preservation of its core scholarly heritage.